Rancang Bangun Sistem Ruangan Cerdas Berbasis IoT dan MQTT Menggunakan Platform Node-RED - Rizky Ade Kusuma; Raymondus Trisaptono; Bryant Valencio Marpaung; Willyam Lucas Haposan Sumual; Abdul Rahman (MDP Student Conference, 2026)
Energy efficiency in modern housing has become a crucial challenge due to user negligence in turning off electrical appliances when not in use. Existing Smart Home automation systems are often constrained by communication latency issues and heavy reliance on manual remote control. This study aims to design and build an IoT-based smart room energy management system that implements hybrid control logic (automatic and manual) using the ESP32 microcontroller. The system integrates sensor fusion between ultrasonic sensors and light intensity sensors (LDR) for precise occupancy detection, as well as a Pulse Width Modulation (PWM) algorithm for fan speed regulation adaptive to room temperature. Data communication is established using the MQTT (Message Queuing Telemetry Transport) protocol connected to a Node-RED dashboard as a real-time monitoring interface. Repeated measurement test results indicate that the system successfully eliminates energy waste with a 100% automatic logic success rate, where lights automatically deactivate when the room is unoccupied. Furthermore, the system demonstrates high responsiveness with an average control command transmission latency of 156.6 ms. The implementation of this system offers an effective solution for energy saving without compromising the thermal and visual comfort of the occupants.